Negative Pressure Wave Leakage Location Algorithm Based on Difference Cross-Correlation Delay Estimation. (October 2019) - Zhao, Lin; Wang, Jiqiang; Hou, Moyu; Li, Zhen
Abstract: Accurate estimate the time difference of the leakage negative pressure wave signals reached both sides of the sensor at the two sides of the leakage point is the key to accurate location of the leakage point. Based on the theoretical analysis of cross-correlation time delay estimation algorithm and characteristics of negative pressure wave signal, a cross-correlation delay estimation method for pipeline leakage negative pressure wave signal is proposed. Through wavelet transform, signal conversion and cross correlation function analysis of discrete negative pressure wave signal sequence obtained by high-speed sampling, the time difference of the negative pressure wave signal monitored by the sensors on both sides of the leakage point can be accurately obtained. In the laboratory's 102.8 meters pipeline, leakage was simulated through the valve, the time delay estimation and leak location experiment of the sensor at the two ends of the pipeline were analyzed, and compared with the wavelet analysis method. The experimental results show under the condition that the leakage is 10%, 5% and 2% of the total pipeline volume, the cross-correlation analysis algorithm has a positioning error interval of 0.97%-1.46%, which is better than the current positioning error 0.48%-2.43% of the wavelet analysis algorithm. At the same time, it avoids the influence of different wavelet types and analysis scales in the wavelet analysis algorithm on positioning accuracy, and is more suitable for pipeline leakage monitoring system to real-time online monitoring needs, has a wide application value.